2019
DOI: 10.2147/ijn.s193176
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functionalized titanium implant in regulating bacteria and cell response</p>

Abstract: Background: Biological complications are an issue of critical interest in contemporary dental and orthopedic fields. Although titanium (Ti), graphene oxide (GO) or silver (Ag) particles are suitable for biomedical implants due to their excellent cytocompatibility, bioactivity, and antibacterial properties, the exact antibacterial mechanism is not understood when the three substances are combined (Ti-GO-Ag). Materials and methods: In this work, the material characterization, antibacterial property, antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Currently, the surface roughness showed no significant variance after mixing with a small dose of Gr ( Figure 1I ). In terms of the “race-for-the-surface,” HGFs gain more advantages than oral pathogens as bacterial adhesion was inclined to reduce due to the surface roughness of Ti-0.125G was regarded as “minimally rough” (Ra < 0.2 μm) ( Albrektsson and Wennerberg, 2004 ; Jin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the surface roughness showed no significant variance after mixing with a small dose of Gr ( Figure 1I ). In terms of the “race-for-the-surface,” HGFs gain more advantages than oral pathogens as bacterial adhesion was inclined to reduce due to the surface roughness of Ti-0.125G was regarded as “minimally rough” (Ra < 0.2 μm) ( Albrektsson and Wennerberg, 2004 ; Jin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thousand μl PBS was replaced with fresh PBS after taking each sample. Fluorescent images of the discs were made using a fluorescent microscope (Leica, Wetzlar, Germany), and fluorescence intensity was quantified using ImageJ software ( https://imagej.net/Fiji.Downloads ) ( Jin et al, 2019 ). Serial dilutions of FITC-BSA in PBS were used as a standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…Jin et al studied the antibacterial effect of Ti-GO-Ag in vitro and in vivo ( Jin et al, 2019 ). The GO group significantly suppressed the bacterial activity of S. mutans and P. gingivalis with the increasing concentration after 24 h. Zhao et al confirmed the antibacterial activity of GO on S. mutans ( Zhao et al, 2020 ).…”
Section: Dental Applications Of Graphene-based Materialsmentioning
confidence: 99%